IDENTIFYING CRIMINALITOR USING FACE DETECTION ON ROOM SECURITY SYSTEM - Robby Yuli Endra; Ade Kurniawan; Ari Kurniawan Saputra (UBL, 2016)
Security is a State where free from danger. because with good security, everyone will feel comfortable and serene setting, so that it became one of the priorities that take precedence. In this research, we will discuss about the facial image recognition systems using Histogram of Oriented Gradient is applied to the face detection system to identify the perpetrators of the crimes. Histogram Of Oriented Gradients is one of the algorithms used to extract object features in the image using the human object, its application in this research is used to detect any pattern of the face. The existence of this system is expected to help law enforcement authorities to identify the perpetrators of crime, face can then be caught in the end the number of crime cases is reduced.